2016
DOI: 10.1002/anie.201604879
|View full text |Cite
|
Sign up to set email alerts
|

Template‐Directed Synthesis of Porous and Protective Core–Shell Bionanoparticles

Abstract: Metal-organic frameworks (MOFs) are promising high surface area coordination polymers with tunable pore structures and functionality;h owever,al acko fg ood sizea nd morphological control over the as-prepared MOFs has persisted as an issue in their application. Herein, we show how arobust protein template,tobacco mosaic virus (TMV), can be used to regulate the sizea nd shape of as-fabricated MOF materials.W ew ere able to obtain discrete rod-shaped TMV@MOF core-shell hybrids with good uniformity,a nd their dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
144
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(148 citation statements)
references
References 62 publications
1
144
0
3
Order By: Relevance
“…Similar phenomenon was observed by Gassensmith and co-workers, where they found that the ZIF-8 film (with a same (4:1) molar ratio of 2-methylimidazole and zinc acetate) was unstable after the sample was removed from mother liquor solution containing the ZIF-8 precursors. 53 Based on this finding, we adjusted the molar ratio of 2-methylimidazole and zinc acetate to 40:1, and observed ~65 nm red shift in the LSPR wavelength (higher than ~55 nm red shift using 4:1 ratio, Figure 5B and 5C) due to the formation of thicker film (~28 nm thickness measured by AFM scratch) (Figure S4D). More importantly, such coatings did not disintegrate after immersing the biochips into DMF or protease solution (Figure 5E and 5F), and thereby the preservation efficacy in both cases was greatly improved (Figure 5A, red bars).…”
Section: Resultsmentioning
confidence: 94%
“…Similar phenomenon was observed by Gassensmith and co-workers, where they found that the ZIF-8 film (with a same (4:1) molar ratio of 2-methylimidazole and zinc acetate) was unstable after the sample was removed from mother liquor solution containing the ZIF-8 precursors. 53 Based on this finding, we adjusted the molar ratio of 2-methylimidazole and zinc acetate to 40:1, and observed ~65 nm red shift in the LSPR wavelength (higher than ~55 nm red shift using 4:1 ratio, Figure 5B and 5C) due to the formation of thicker film (~28 nm thickness measured by AFM scratch) (Figure S4D). More importantly, such coatings did not disintegrate after immersing the biochips into DMF or protease solution (Figure 5E and 5F), and thereby the preservation efficacy in both cases was greatly improved (Figure 5A, red bars).…”
Section: Resultsmentioning
confidence: 94%
“…[10] Unfortunately,t he surface charge and chemistry of the protein strongly determined its ability to be encapsulated into the MOFs:o nly those with al ow surface electrostatic potential were capable of concentrating the metal cations and inducing the encapsulation process. [10] Unfortunately,t he surface charge and chemistry of the protein strongly determined its ability to be encapsulated into the MOFs:o nly those with al ow surface electrostatic potential were capable of concentrating the metal cations and inducing the encapsulation process.…”
mentioning
confidence: 99%
“…Encasing ap rotein within aM OF that possessed significantly smaller pore dimensions than the biomacromolecule was recently achieved via am ild de novo approach, such as biomimetic mineralization. [10] Unfortunately,t he surface charge and chemistry of the protein strongly determined its ability to be encapsulated into the MOFs:o nly those with al ow surface electrostatic potential were capable of concentrating the metal cations and inducing the encapsulation process. [11] Moreover,there are cases in which it takes along time (several days) to induce MOF formation.…”
mentioning
confidence: 99%
“…After the synthesis, it is crucial to clearly demonstrate the structure of 2D MOF nanosheets. Although the crystal structures of MOFs were usually solved by the precise measurements with the single crystal X‐ray diffraction technique or the combined agreement between simulation and refinement with powder X‐ray diffraction (XRD), there are still no decisive single technique to determine the structure of 2D MOF nanosheets . The combination of multiple techniques was normally employed for the characterization.…”
Section: Synthesis and Characterization Methodologiesmentioning
confidence: 99%
“…Although the crystal structures of MOFs were usuallys olved by the precise measurements with the single crystal X-ray diffractiont echnique or the combined agreement between simulation and refinement with powderX -ray diffraction( XRD), there are still no decisives ingle technique to determine the structure of 2D MOF nanosheets. [45,65,66] www.chemeurj.org 2018 Wiley-VCH Verlag GmbH &Co. KGaA, Weinheim whose X-ray diffraction patternsh ave to agree with their simulated ones. [57,67] Then the morphology of the nanosheets can be characterized by transmission electron microscope (TEM), scanninge lectron microscope (SEM), and atomicf orce microscope (AFM).…”
Section: Introductionmentioning
confidence: 99%